The Role of Local Materials in Creating A Meaningful Visual Experiences in Urban Public Facilities - Mustikawati Triandriani; Sengke Maria M.C; Atmodiwirjo Paramita; Yatmo Yandi Andri (MATEC Web of Conferences, 2019)
This paper discusses visibility potential of local material products that are used as part of architectural spaces. Knowing the visibility potential of local materials is essential to create visual clarity that supports the ease of spatial orientation and navigation and provides a meaningful visual experience in urban public facilities. This study aims at finding the property quality of objects from local materials that contribute to the visibility potential. Field studies were conducted to identify different types of products from local materials and their characteristics associated with the quality of space experience. The visibility analysis using 3D software program then was carried out by simulating the placement of objects as elements of space in a particular spatial configuration. The result reveals several patterns of possible placement of objects from local materials that have the best potential to enhance visibility. These patterns can add to the alternative vocabulary in architectural design.